In Vitro Wound Healing Effect of Asiaticoside Extracted from Centella asiatica (‘Pegaga’) on Human Gingival Fibroblast Cell Line - Suriyah, Wastuti Hidayati; Rizal, Aisyah Juares; Mohamed Nadzirin, Hana Syakirah; Arief Ichwan, Solachuddin Jauhari; Md Isa, Muhammad Lokman (Trans Tech Publications Ltd., 2021)
Abstract. Asiaticoside is a bioactive compound found in the traditional plant Centella asiatica (Asiatic pennywort or ‘Pegaga’) generally used for wound healing applications. Numerous studies have discussed the potential benefits of asiaticoside on different human cells such as keratinocytes and dermal fibroblast cells in healing of wounds. However only very few studies have been conducted to investigate its healing effect on cells originated from human oral cavity. The present study aimed to determine the potential of asiaticoside on human gingival fibroblast cells. Cytotoxic activities of the compounds were assessed by MTT assay. The wound healing was examined by scratch assay. The effect of asiaticoside on Col1A1 gene expression was also analyzed using qRT-PCR. Col1A1 is known to play a crucial role in wound healing. The MTT assay result showed that the maximum tolerable concentration of asiaticoside was 0.25 mg/ml. The scratch assay revealed that asiaticoside significantly accelerated the wound healing compared to the negative control (P<0.05). Moreover, the qRT-PCR demonstrated that asiaticoside markedly increased Col1A1 mRNA expression. These results proved asiaticoside as a potential candidate for wound healing agent in dentistry.